The Rubble of Culture Debris of an Extinct Thought - Collings, David A. (CCC2 Irreversibility, 2023)
Humanity now faces the possibility that it will become extinct over the next few decades or so. This is not simply a reality about the biological fate of the species; it also raises the prospect of thought's own extinction. But what does it mean for thought that it, too, might disappear? Thought's possible disappearance shatters the assumption, at work across all the institutions and disciplines of the West, that one version or another of thought is enduring and will survive. As it turns out, no familiar practice rests on a secure ground; under the sign of the terminus - the prospect of humanity's extinction - each one is shattered and undone. The cultural legacy becomes a field of rubble. In dozens of short essays, this book moves through this field. It takes up a host of specific inheritances and traces how each is shattered and transformed by an extinct thought. It engages with religion, philosophy, history, literature, ethics, studies of political power and resistance, and depictions of humanity's place in the nonhuman world. It reconsiders the emergence of capitalism and of biopower, the science of climate change, the import of mediation and technology, and philosophies of temporality. Moreover, it contends with many innovative waves of thought over the past two centuries, from German idealism to deconstruction, from psychoanalysis to queer theory, from decolonizing theory to Afropessimism, and from the critique of ideology to speculative realism. It concludes by assessing what it is like for thought, having confronted its extinction, to live on in this debris, to dance with its own oblivion.